The forgotten key players in rheumatoid arthritis: IL-8 and IL-17 – Unmet needs and therapeutic perspectives - Gremese, Elisa; Tolusso, Barbara; Bruno, Dario; Perniola, Simone; Ferraccioli, Gianfranco; Alivernini, Stefano (Frontiers in Medicine, 2023)
Despite the relevant advances in our understanding of the pathogenetic mechanisms regulating inflammation in rheumatoid arthritis (RA) and the development of effective therapeutics, to date, there is still a proportion of RA patients who do not respond to treatment and progress towards the development of joint damage, extra-articular complications and disability. This is mainly due to the inter-individual heterogeneity of the molecular and cellular taxonomy of the synovial membrane which represents the target tissue of RA inflammation. Tumor necrosis factor alpha (TNFa) and interleukin-6 (IL-6) are crucial key players in RA pathogenesis fueling the inflammatory cascade as supported by experimental evidence derived from in vivo animal models and the effectiveness of biologic-Disease Modifying Anti-Rheumatic Drugs (b-DMARDs) in RA patients. However, additional inflammatory soluble mediators as IL-8 and IL-17 exert their pathogenetic actions promoting the detrimental activation of immune and stromal cells in RA synovial membrane, tendons and in extra-articular sites, as blood vessel and lung, causing extra-articular complications, which might be excluded by the action of anti-TNFa and anti-IL6R targeted therapies. In this narrative review, we will discuss the role of IL-8 and IL-17 in promoting inflammation in multiple biological compartments (i.e. synovial membrane, blood vessels and lung respectively) in animal models of arthritis and in RA patients and how their selective targeting could improve the management of the resistant to treatment patients.